Sea ice concentration off Dronning Maud Land, Antarctica - Pavlova, Olga; Winther, Jan-Gunnar (Norsk Polarinstitutt, 2002)
This project was undertaken by the Norwegian Polar Institute for the Norwegian Petroleum Directorate (Oljedirektoratet) as support for planning of marine geophysical surveys offshore from Dronning Maud Land (DML), Antarctica. The project was carried out by scientists Olga Pavlova and Jan-Gunnar Winther at the Norwegian Polar Institute under the direction of Morten Sand at the Norwegian Petroleum Directorate. The main objectives of the project were to: a) calculate 10-day average historical (i.e., 1978-1996) sea ice concentrations off DML for the months of December through April b) identify the minimum and maximum sea ice extent occurring in the period 1978-1996 c) present the above information graphically. Daily microwave satellite data covering the period 1978-1996 with 25 x 25 km spatial resolution were used as basis for this study (see text below for description of data set).
Keywords: Dronning Maud Land; havis; kartlegging; marin geofysikk; meteorologi; sjøis

Report of the Norwegian Antarctic Research Expedition 1989/90 - Norsk, Polarinstitutt (Norsk Polarinstitutt, 1990)
Keywords: Antarktis; Dronning Maud Land; NARE 1989/90; Troll forskningsstasjon; Weddellhavet; geologi; marin økologi; meteorologi; zoologi

A 200-Year Record of Glacier Mass Balance at Deception Island, Southwest Atlantic Ocean, and Its Bearing on Models of Global Climatic Change - Orheim, Olav (The Ohio State University, 1972)
Keywords: Antarktis; ekspedisjoner; glasiologi; isbreer; klimaendringer; meteorologi; storbreen; stratigrafi

The 2nd tropopause : a statistical and physical study - Harsson, Bjørn Geirr (Norsk Polarinstitutt. Skrifter, 1971)
Keywords: Antarktis; Den Norske Antarktisekspedisjonen 1956-60; Det internasjonale geofysiske år 1957-58; IGY 1957-58; atmosfæren; ekspedisjoner; forskning; meteorologi; observasjoner

International Weddell Sea oceanographic expedition : position and weather journal USCGC Glacier - Kvinge, Thor (University of Bergen, 1970)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; fysisk oseanografi; meteorologi; oseanografi

IWSOE - 69 : position and weather journal USCGC "Glacier" - Kvinge, Thor (University of Bergen, 1969)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; fysisk oseanografi; meteorologi; oseanografi

Climate data for Norway Station and SANAE in the Antarctic for the years 1960 to 1965 (Weather Bureau. Department of Transport, 1965)
This table contains data for Norway Station from January 1960 to January 1962 inclusive, and for SANAE from April (or in some cases June) 1962 to December 1965. A Norwegian type of screen, equipped with a fan, is used for housing the instruments. Air temperatures are measured by means of mercury, thallium and alcohol thermometers; and humidity readings are derived from the records of a Foxboro temperature and dew-point recorder, and sometimes also a hair hygrograph. Wind direction and speed at a height of 10 meters are obtained from a Munro type cup anemometer recording indoors. For the measurement of sunshine, a Fuess-type recorder with two glass spheres and a built-in heater is used. Barometric pressure is obtained from an ordinary Kew-type mercury barometer. (Auth.)
Keywords: Dronning Maud Land; klimatologi; meteorologi

On the radiation balance and micrometeorological conditions at Norway station, Antarctica - Vinje, Torgny E (Norsk Polarinstitutt, 1964)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; meteorologi; stråling

Meteorological observations made on 9 Norwegian whaling floating factories during The International Polar Year 1932-1933 - Harang, Leiv; Hesselberg, Th. (Det norske meteorologiske institutt, 1935)
Keywords: Det internasjonale polaråret; Sørishavet; hvalfangst; meteorologi

Norvegia rundt sydpollandet : Norvegia-ekspedisjonen 1930-1931 - Isachsen, Gunnar (Gyldendal, 1934)
Keywords: Antarktis; Hjalmar Riiser; Lars Christensen; Larsen; Norvegia ekspedisjonen; Sydpolen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; meteorologi; oppdagelsesreiser; oseanografi

I. Norske undersøkelser ved Sydpollandet 1929-1931. II. Norvegia-ekspedisjonen 1930-1931 : omseilingen av Sydpollandet - Isachsen, Gunnar (1931)
Keywords: Antarktis; Hjalmar Riiser; Lars Christensen; Larsen; Norvegia ekspedisjonen; Sydpolen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; meteorologi; oppdagelsesreiser; oseanografi

Luftdruck zu Framheim und seine tägliche Periode - Mohn, Henrik (Dybwad, 1916)
Keywords: Antarktis; Sydpolsekspedisjonen; meteorologi

Meteorology - Mohn, Henrik (Dybwad, 1915)
Keywords: Antarktis; Sydpolsekspedisjonen; meteorologi

Magnetic and meteorological observations made by the "Southern Cross" Antarctic expedition 1898-1900 - Borchgrevink, Carsten Egeberg; Bernacchi, Louis (Royal Society of London, 1902)
Keywords: Antarktis; Southern Cross; ekspedisjonen; ekspedisjoner; forskning; magnetisme; meteorologi; observasjoner; oppdagelsesreiser; polarekspedisjoner

Om Polarforskning - Mohn, Henrik (Selskabet for Folkeoplysningens Fremme, 1897)
Keywords: Antarktis; meteorologi; polarforskning; polarområdene